Pedagogical, Personality, Social and Professional Competence in Correlation with Teachers’ Performance (Correlational Study of Junior High School Teacher at SMPN 3 Purwokerto) - Taniredja, Tukiran; Abduh, Muhammad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
The purpose of this research was: (1) to determine the effects of each professionalism competence (pedagogical, personal, professional, and social competency) on the teachers’ performance at SMP Negeri 3 Purwokerto Junior High School; (2) to determine the effects of overall professionalism competence (pedagogical, personal, professional, and social competency) on the teachers’ performance at SMP Negeri 3 Purwokerto Junior High School; and (3) to determine the most significant factor of pedagogical, personal, professional, and social on teachers’ performance at SMP Negeri 3 Purwokerto Junior High School. The subject of this study was all teachers of SMP Negeri 3 Purwokerto Junior High School consisting of 39 teachers. A questionnaire was used to collect the data and diagram track/path diagram was used to analyze the data. The results of the study showed that there were significant effects of the pedagogical, personal, professional and social on teachers’ performance at SMP Negeri 3 Purwokerto Junior High School; and among all competences, the dominant factor in the teachers’ performance at SMP Negeri 3 Purwokerto Junior High School was the social competence.